METHODS OF FORMING ELEMENTS OF NATIONAL VALUES IN STUDENTS THROUGH EDUCATION - Olimova Nilufar Qosimjon qizi; A’zamjonova Mehrinoz Bahodir qizi (Western European Studies, 2025)
In all periods of social development, the content and direction of education are determined by the harmony of universal values. Educating and raising students who are mentally mature, morally pure, physically strong, and aware of a sense of national responsibility creates the basis for the independent and sustainable development of the country. National education cannot develop in isolation from universal values. Schools of educational methodology are developing and gaining content. In the current era, the task of educating the spirituality of the individual requires raising the work of effectively organizing the discipline of education in schools to a qualitative level. Today, we will try to reveal the extremely important goals and tasks of the discipline of education.
Keywords: Education; national values; education of students